Insights Into Antioxidant Strategies to Counteract Radiation-Induced Male Infertility - Spadella, Maria Angélica; Silva, Erick J.R. [UNESP]; Chies, Agnaldo Bruno; Almeida, Laine Andreotti de (SAGE Publications, 2024)
Significance: Radiotherapy, which employs ionizing radiation to destroy or prevent the multiplication of tumor cells, has been increasingly used in the treatment of neoplastic diseases, especially cancers. However, radiation collaterally leads to prolonged periods of sperm count suppression, presumably due to impaired spermatogenesis by depleting the germ cell pool, which has long-term side effects for male reproduction. Recent Advances: Studies of antioxidant compounds as a potential strategy for male fertility preservation have been performed mainly from animal models, aiming to prevent and restore the male germinal tissue and its function, particularly against the oxidative stress effects of radiation. Evidence in preclinical and clinical trials has shown that inhibitors of the renin-angiotensin system and other drugs, such as statins and metformin, are candidates for ameliorating radiation-induced damage to several tissues, including the testis and prostate. Critical Issues: Research for developing an ideal radioprotective agent is challenging due to toxicity in the normal tissue, tumor radioresistance, cellular response to radiation, costs, regulation, and timeline development. Moreover, male radioprotection experiments in humans, mainly clinical trials, are scarce and use few individuals. This scenario is reflected in the slow progress of innovation in the radioprotection field. Future Directions: Expanding human studies to provide clues on the efficacy and safety of radioprotective compounds in the human reproductive system is necessary. Drug repurposing, frequently used in clinical practice, can be a way to shorten the development pipeline for innovative approaches for radioprotection or radiomitigation of the repercussions of radiotherapy in the male reproductive system.
Keywords: drug repurposing; free radicals; ionizing radiation; male fertility; oxidative stress; testis